Women entrepreneurship in South Africa : motivations, challenges and ways to improve conditions - Mushoma, Tsireledzo (My University, 2018)
Entrepreneurship has been highlighted as one of the leading contributors to economic growth through job creation and increase in innovation. However, entrepreneurs must overcome barriers such as the lack of finance which usually threaten the survival of their ventures. Previous studies have shown that women entrepreneurs are the worst-affected. They face additional barriers such as cultural values that discourage women entrepreneurship and gender discrimination. The purpose of this research is therefore to explore the motivating factors and challenges of South African women entrepreneurs, and how the nuanced understanding of motivating factors and challenges can be used to improve the state of women entrepreneurship in South Africa, and consequently engender women to actively venture into entrepreneurship. Interviews with women entrepreneurs were conducted to get an in-depth understanding of the entrepreneurial conditions, primarily focusing on barriers women face, factors motivating women to venture into entrepreneurship, and ways to improve conditions for women. The results of the study show that women entrepreneurs in South Africa are motivated by job dissatisfaction, unemployment, the need for independence, need to increase income, entrepreneurial inclination and the pursuit of a hobby. Challenges that women entrepreneurs face are related to lack of access to networking opportunities, markets, funding and knowledge. Other barriers include gender discrimination and corruption. The study contributes to the field of women entrepreneurship by making recommendations about how an understanding of entrepreneurial motivation can be a useful indicator of the kind of support women entrepreneurs need. This knowledge can help improve conditions for women entrepreneurs. In the context of limited resources, efforts aimed at supporting women entrepreneurs should be effective if there is an awareness of their actual needs.
MBA Thesis
Keywords: women entrepreneurs, female entrepreneurship, motivational factors, challenges, South Africa